1.3 Sheets - ?Best Practice? Methodology For Production And Use Of Reference Materials For The Platinum Industry. - Ron Sheets; David Grant; Gordon Chunnett (The Southern African Institute of Mining and Metallurgy, 2005)
[Power-Point Presentation]